(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
India places a high priority on the Ganga’s economic, environmental, and cultural contributions. The river flows across the plains of north and eastern India for more than 2,500 kilometres before emptying into the Bay of Bengal after rising in the Himalayas. One of the holiest rivers in India, the Ganga has cultural and spiritual importance that extends beyond of the basin. Despite its significance, the Ganga’s biodiversity and environmental sustainability are seriously threatened by the tremendous pollution pressures caused by rising population and industrialisation, which have a negative impact on both the quantity and quality of its flows. The primary causes of pollution in the Ganga River include the discharge of untreated sewage and industrial wastewater, non-point pollution sources from religious activities near the river, agricultural runoff and livestock, as well as inadequate municipal solid waste management.